2022
DOI: 10.1177/17588359221103212
|View full text |Cite
|
Sign up to set email alerts
|

Improving the tolerability of osimertinib by identifying its toxic limit

Abstract: Background: Osimertinib is the cornerstone in the treatment of epidermal growth factor receptor-mutated non-small cell lung cancer (NSCLC). Nonetheless, ±25% of patients experience severe treatment-related toxicities. Currently, it is impossible to identify patients at risk of severe toxicity beforehand. Therefore, we aimed to study the relationship between osimertinib exposure and severe toxicity and to identify a safe toxic limit for a preventive dose reduction. Methods: In this real-life prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Albumin level was identified as a significant covariate for the clearance of the parent compound and AZ5104 (positive correlation), consistent with a previous report [ 29 ]. C-reactive protein (CRP) is a covariate of osimertinib clearance [ 21 ]. Decrease in albumin level and an increase in CRP level occur during inflammation, which can decrease CYP3A4 activity [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albumin level was identified as a significant covariate for the clearance of the parent compound and AZ5104 (positive correlation), consistent with a previous report [ 29 ]. C-reactive protein (CRP) is a covariate of osimertinib clearance [ 21 ]. Decrease in albumin level and an increase in CRP level occur during inflammation, which can decrease CYP3A4 activity [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Funding This work was supported by the Research Foundation for Pharmaceutical Sciences, the Japan Research Foundation for Clinical Pharmacology (grant number 2018A20), JST SPRING (grant number JPMJSP2123), and the Keio University Doctorate Student Grant-in-exposure to osimertinib and efficacy, dose reduction up to 50% of mean exposure may be considered for patients experiencing AEs and high AUC 0-24 levels; however, further validation is needed [11,21,40,42].…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Agema et al reported 259 ng/ml as the osimertinib dose limit for toxicity in a prospective observational study of 159 patients with NSCLC in Netherlands (26). Major adverse events such as skin toxicities, creatinine kinase elevation, and pneumonia were significantly higher in patients with plasma osimertinib concentrations of >259 ng/ml; however, the authors did not observe a difference in efficacy possibly because the plasma osimertinib concentrations exceeded 211 ng/ml in most patients.…”
Section: Discussionmentioning
confidence: 97%
“…A more general approach, of boosting osimertinib exposure purely based on the plasma trough concentration, to improve osimertinib effectiveness is less evident, as a definitive exposure-response relation seems absent for osimertinib. Especially boosting in patients with initially high osimertinib exposure may be less ideal, as it could this could lead to a higher level of toxicity (≥259 ng/mL) [27]. However, inhibiting CYP3A-activity could theoretically increase the anti-tumor activity of osimertinib, as intratumoral CYP3A activity would be inhibited, which is increased in NSCLC-patients [28].…”
Section: Discussion (1070 Words)mentioning
confidence: 99%